Risk factors of sepsis after open congenital cardiac surgery in infants: a pilot study (Medical Journal of Indonesia, 2016)
Background: Postsurgical sepsis is one of the main causes of the high mortality and morbidity after open congenital heart surgery in infants.This study aimed to evaluate the role of cardiopulmonary bypass duration, thymectomy, surgical complexity, and nutritional status on postsurgical sepsis after open congenital cardiac surgery in infants. Methods: A total of 40 patients <1 year of age with congenital heart disease, Aristotle Basic Score (ABS) ≥6 were followed for clinical and laboratory data before and after surgery until the occurrence of signs or symptoms of sepsis or until a maximum of 7 days after surgery. Bivariate analyses were performed. Variables with p≤0.200 were then included for logistic regression. Results: Duration of cardiopulmonary bypass ≥90 minutes was associated with 5.538 increased risk of postsurgical sepsis in comparison to those ≤90 minutes (80% vs 25%, RR=5.538, p=0.006). No association was observed between the incidence of postsurgical sepsis with poor nutritional status (86% vs 84%, RR=1.059, p=1.000), thymectomy (and 50% vs 76%, RR=0.481, p=0.157), and Aristotle Basic Score (p=0.870). Conclusion: Cardiopulmonary bypass time influences the incidence of sepsis infants undergoing open congenital cardiac surgery. Further studies are needed to elaborate a number of risk factors associated with the incidence of sepsis in this population.